2007
DOI: 10.1016/j.susc.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

In situ XPS investigation of Pt(Sn)/Mg(Al)O catalysts during ethane dehydrogenation experiments

Abstract: Calcined hydrotalcite with or without added metal (Mg(Al)O, Pt/Mg(Al)O and Pt,Sn/Mg(Al)O) have been investigated with in situ X-ray Photoelectron Spectroscopy (XPS) during ethane dehydrogenation experiments. The temperature in the analysis chamber was 450ºC and the gas pressure was in the range 0.3 -1 mbar. Depth profiling of calcined hydrotalcite and platinum catalysts under reaction, oxidation and in hydrogenwater mixture was performed by varying the photon energy, covering an analysis depth of 10-21 Å. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 48 publications
11
40
1
Order By: Relevance
“…After exposure to 300 mbar H 2 at RT for 2 h the Pt become fully metallic and about 60 % of the tin content was reduced to Sn 0 showing a Sn 3d 5/2 binding energy of 485.3 eV. This value is somewhat high for bulk metallic Sn (485.0 eV or below), but corresponds well to those reported for Pt-Sn alloys [48][49][50]. The somewhat low Sn M 4 N 45 N 45 Auger kinetic energy (436.0 eV giving an Auger parameter of 921.5 eV) is still compatible with a metallic environment; the shift from the bulk metallic value is again indication of Sn-Pt alloy formation.…”
Section: Xps Analysis Of the Sn-20pt/c Electrocatalystssupporting
confidence: 83%
See 1 more Smart Citation
“…After exposure to 300 mbar H 2 at RT for 2 h the Pt become fully metallic and about 60 % of the tin content was reduced to Sn 0 showing a Sn 3d 5/2 binding energy of 485.3 eV. This value is somewhat high for bulk metallic Sn (485.0 eV or below), but corresponds well to those reported for Pt-Sn alloys [48][49][50]. The somewhat low Sn M 4 N 45 N 45 Auger kinetic energy (436.0 eV giving an Auger parameter of 921.5 eV) is still compatible with a metallic environment; the shift from the bulk metallic value is again indication of Sn-Pt alloy formation.…”
Section: Xps Analysis Of the Sn-20pt/c Electrocatalystssupporting
confidence: 83%
“…The smaller than expected Pt/Sn ratio indicates that metallic tin still remains a surface species. According to the literature, surface segregation of tin in Pt-Sn alloys is a known property [50,51]; the nature of the segregation seems to be also related to the Pt particle size [52]. As it is shown in Fig.…”
Section: Xps Analysis Of the Sn-20pt/c Electrocatalystsmentioning
confidence: 94%
“…Previous studies showed that metal oxide supports including K-L zeolite, spinels, alkali-doped alumina, calcined hydrotalcite greatly suppressed coke formation due to the free of acid sites and low alkene adsorption [32][33][34][35][36][37]. Among these supports, the studies about the calcined hydrotalcite (Mg(Al)O) or hydrotalcite-like materials were especially attractive due to their moderate basic characteristics and high thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of LDH as catalyst precursors list the possibility to use various cationic pairs in the formation of a layered structure and hence the synthesis of materials with different controllable properties; the distribution of cations in the LDH structure at the atomic level, which prevents their significant segregation during further treatments; and the formation of mixed oxides with a developed surface area upon decomposition of LDH. The application of mixed oxides produced by thermal treatment of magnesium-aluminum LDH as non-acid supports for platinum catalysts ensures the high stability of the catalysts under the coking conditions and during the redox treatment [11,12]. Thus, one of the promising applications of such catalysts is the hightemperature dehydrogenation of alkanes [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%